Effectiveness Performance in accordance with Good Governance Principles’ Personnel of Boploy Subdistrict Administrative Organization, Boploy District, Kanchanaburi Province - Jantarasakha, Ornpapat (Arts of Management Journal, 2021)
This article aimed 1) to study the effectiveness of performance in accordance with the good governance principles’ personnel of Boploy Sub-district Administrative Organization, Boploy District, Kanchanaburi Province; 2) to study the management characteristics according to with the good governance principles’ personnel of Boploy Sub-district Administrative Organization, Boploy District, Kanchanaburi Province; and 3) to compare people's opinions on the effective performance in accordance with the good governance principles’ personnel with different gender, marital status, education, age, occupation, and monthly income. The population of this study was 7,129 people living in Boploy Sub-district Administrative Organization, Boploy District, Kanchanaburi Province, and sampling by using Taro Yamane's calculation formula, totaling 379 people by the descriptive statistic. It was a preliminary analysis to describe the general information characteristics of the respondents by presenting in the form of a percent, mean, standard deviation (SD), and inferential statistic. The statistics used to test the hypothesis with a t-test and a simple correlation test to calculate the relationship between 2 variables from the Pearson correlation formula. The research results were found as follows: 1) The effectiveness of performance in accordance with good governance principles’ personnel of Boploy Sub-district Administrative Organization, Boploy District, Kanchanaburi Province in all aspects was at a high level and when considering each aspect, it was found that all aspects of the people's health benefits in terms of efficiency and cost-effectiveness in terms of government missions and reducing operating procedures at a high level. 2) People had opinions about the administration, according to the principles of good governance of Boploy Sub-district Administrative Organization, Boploy District, Kanchanaburi Province. Overall was at a high level. 3) The results of comparing people's opinions on the effectiveness of work in accordance with the principles of good governance of personnel. Different personal data showed that the difference between sex and age was statistically significant at .05 level, marital status, occupation, education level Different monthly income was found to be no different. 4) The results of comparing the relationship between the principles of good governance and the effectiveness of operations, according to the principles of good governance were found that they are positively correlated and were at a high level.